Pancasila sebagai paradigma pembangunan nasional dalam kehidupan berbangsa dan bernegara - Rahmadhani, Fadilah Eka (Maliki Interdisciplinary Journal, 2025)
This study aims to comprehensively analyze the central role of Pancasila as a paradigm for national development in Indonesia. Pancasila has a fundamental position, not only as the philosophical and ideological basis of the state, but also as a normative framework that guides the entire process of planning, implementing, and evaluating development. National development is measured from a holistic dimension, covering material growth as well as holistic human development (moral, social, and spiritual), which must be based on the values of divinity, humanity, unity, democracy, and social justice. Theoretically, Pancasila functions as a comprehensive framework that encompasses normative, ideological, and practical aspects to integrate all sectors of national development (politics, law, economy, socio-culture, defense) in order to achieve the ideal of a just and prosperous society. However, its implementation faces major challenges. Internally, this is due to inconsistent political commitment and a lack of understanding. Externally, implementation is hampered by the erosion of national values as a result of globalization and liberalization. Thus, reinforcing Pancasila as a strategic foundation is a necessity. This step is important to balance material and spiritual progress in order to realize development that is just, sustainable, and in line with Indonesia’s character.